Health equity in Brazil : intersections of gender, race, and policy - Caldwell, Kia Lilly, 1971- (Urbana : University of Illinois Press, 2017)
"This project examines how structural and institutional factors contributed and continue to contribute to poor health outcomes for scores of nameless Afro-Brazilian women and men. Despite having the second largest African-descendant population in the world, Brazil failed to develop policies to address health issues that disproportionately affect Afro-Brazilians until the early 21st century. Additionally, Brazil does not have a long tradition of research or policies focusing on racial or ethnic health disparities. While the country has risen to become a world leader in the fight against HIV/AIDS, it continues to face ongoing challenges in ensuring health equity for Afro-Brazilians. This project highlights how Brazil has succeeded and failed at certain challenges in its quest to provide quality healthcare for all its citizens, but particularly to Afro-Brazilian women and men, and examines the development of the feminist health movement and black women's movement, which developed significant policy interventions related to women's health. Kia Caldwell assembles a policy history of Brazilian feminist health movement to analyze how health activists and policy makers have attempted to address gender and racial health inequities from the early 1980s to the present."--Provided by publisher.
6 Making Race and Gender Visible in Brazil's HIV/AIDS Epidemic: Policy, Advocacy, and ResearchConclusion; Notes; Bibliography; Index.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on February 16, 2018).
eBooks on EBSCOhost
Keywords: Public health -- Brazil; Women -- Health and hygiene; Health Equity -- history; History, 21st Century; History, 20th Century; Women's Health; Socioeconomic Factors -- history; Sexism; Racism; Health Policy -- history; Black People; Santé publique -- Brésil.; Médecine -- Histoire -- 21e siècle.; Médecine -- Histoire -- 20e siècle.; Femmes -- Santé et hygiène.; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; SOCIAL SCIENCE -- General; Women -- Health and hygiene; Public health; Brazil